Chandler P. Anderson papers - Anderson, Chandler P. (Chandler Parsons), 1866-1936.
Correspondence, diaries, minutes of meetings, writings, reports, informal records and notes of negotiations, transcripts of court proceedings and other legal records, press releases, clippings, print and near-print material, maps, and other papers relating chiefly to Anderson's career in international law and official activities in the U.S. Dept of State. Includes summaries of conversations with Bernard M. Baruch, Robert Lansing, Henry Cabot Lodge, Elihu Root, and Woodrow Wilson. Subjects include relations between the United States and Great Britain; public and official opinion in Great Britain during World War I; the peace treaty with Germany, 1921; the League of Nations; American economic interests in the Soviet Union in the 1920s; the Conference on the Limitation of Armament, Washington, D.C., 1921-1922; boundary problems between Central American countries; internal problems in Nicaragua during the 1920s; and inland and international fisheries negotiations. Correspondents include William Jennings Bryan, Otis T. Cartwright, Charles Evans Hughes, David Starr Jordan, Philander C. Knox, Robert Lansing, Frank L. Polk, Elihu Root, James Brown Scott, and Charles Beecher Warren.
Microfilm of diaries (1914-1928, 1934) available
Microfilm produced from originals in the Manuscript Division.
Lawyer, advisor to the U.S. Dept. of State, and international arbitrator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Correspondence between Anderson and Robert Lansing was transferred to the Manuscript Division's Robert Lansing papers.
Keywords: Baruch, Bernard M. -- 1870-1965.; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Cartwright, Otis T. -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Jordan, David Starr, -- 1851-1931 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; Lansing, Robert, -- 1864-1928.; Lansing, Robert, -- 1864-1928 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924; Polk, Frank L. -- 1871-1943 -- Correspondence; Root, Elihu, -- 1845-1937.; Root, Elihu, -- 1845-1937 -- Correspondence; Scott, James Brown, -- 1866-1943 -- Correspondence; Warren, Charles Beecher -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Germany. -- 1921 August 25.; United States. -- Department of State; United States. -- Department of State -- Officials and employees; League of Nations; Boundaries; Disarmament; Fishery law and legislation; International law; International relations; Investments, American -- Soviet Union; World War, 1914-1918 -- Peace; World War, 1914-1918 -- Great Britain; Central America -- Boundaries; Germany -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; Nicaragua -- History -- 1909-1937.; United States -- Foreign relations -- Germany; United States -- Foreign relations -- Great Britain; International arbitrators; Lawyers; Public officials